Uso de tecnologías emergentes en la enseñanza de la realidad urbana FAUD UNC Córdoba, Argentina - Mariconde, María Marta (Universidad de Boyacá, 2019)
In the section "Dissertations on Design" of Vol 7, No. 1 of Designia magazine, the invited authors present a short article of reflection, in which pedagogical practices with emerging technologies are exposed in the subject of Morphology III: Urban Morphology, of the FAUD National University of Córdoba, Argentina. The experimental workshop takes as an object of study the North Market sector of the city of Córdoba and there proposes the development of city readings, focused on the analysis of urban color, under the didactic application of technological tools such as devices, mobile applications and internet. The proposed methodology includes the development of a collaborative digital mapping of the sector, a relief of the perceived digital color and the conceptualization of the results from a synthesis video. The experience results allow us to visualize the advantages of the educational trend of mobile learning and the use of technological resources. It is considered that the exercise motivates and stimulates the teaching and learning processes and promotes the collaborative construction of knowledge.